If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -13 = -1x + 15 Reorder the terms: -13 + 3x = -1x + 15 Reorder the terms: -13 + 3x = 15 + -1x Solving -13 + 3x = 15 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -13 + 3x + x = 15 + -1x + x Combine like terms: 3x + x = 4x -13 + 4x = 15 + -1x + x Combine like terms: -1x + x = 0 -13 + 4x = 15 + 0 -13 + 4x = 15 Add '13' to each side of the equation. -13 + 13 + 4x = 15 + 13 Combine like terms: -13 + 13 = 0 0 + 4x = 15 + 13 4x = 15 + 13 Combine like terms: 15 + 13 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 20x+12z=30 | | 8x-13=6x-3 | | -x-3=-4x-9 | | x(-2)=(-18) | | x-8=-2x+22 | | 5(a+4)-3.2=14.3 | | x-16=-x-30 | | 5x-4=-2x-25 | | -3x-17=-44 | | 8x-7=3x-17 | | x+(.4x*.5x*.145x)=19130 | | Y=-0.8t+40 | | 8x+14=4x+34 | | 113-303= | | 33(-5)= | | 6=-10d+2 | | 33x-5= | | 2x^2-4x+103=0 | | 2x^2-4x-103=0 | | 6-7d=-3D+2 | | 15-2x=0 | | -6x^2-2x-1=0 | | 8=-5x-3 | | -366+k=170 | | 17+4(3+q)-a= | | 3x-5(0.6x-1)=3 | | 4(3+9)+10a-41= | | M+-2=67 | | 6x-24=4x-2-6 | | 2(3-3x)=94 | | 6x+8+2x=4(5+x) | | 3f+47-2f=40 |